KORELASI AMBANG NYERI TEKAN OTOT DENGAN DERAJAT NYERI DAN DISABILITAS PADA PENGENDARA OJEK ONLINE YANG MENDERITA NYERI PUNGGUNG BAWAH MIOFASIAL - Mirna Marhami Iskandar; Attiya Istarini (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
Background: Online taxi rider is one of the jobs that requires the rider to be in a sitting or flexed position for a long time. An ergonomic position at work affects the pressure and tension of the lower back muscles. Continuous muscle pressure and strain has the risk of causing myofascial low back pain (LBP) in Online taxi riders. Objectives: This study aims to determine the correlation between the pressure threshold and the degree of pain and degree of disability in online motorcycle taxi drivers who suffer from LBP. Methods: This study is an observational study with a cross-sectional design. All samples were examined for muscle pressure at trigger points at paraspinal mucle in the lower back area using an Algometer. Assessment of the degree of pain was carried out using the Numeric Pain Scale instrument and the degree of disability was assessed by the Oswetri Disability Index. Results: In this study, 30 online Online taxi riders were found with complaints of myofascial low back pain with an average pressure threshold that causes pain at the trigger point of 5.03 Â± 1.3 kgf. After conducting bivariate analysis with the Pearson test, no significant correlation was found between the threshold of muscle tension and the degree of pain and degree of disability of Online taxi riders who suffer from LBP (p>0.05). Conclusion: There is no correlation between the threshold of muscle pressure and the degree of pain and disability of Online taxi rider. Keywords: threshold of tenderness, myofacial lower back pain, online taxi riders